Immune checkpoint inhibition for non-small cell lung cancer in patients with pulmonary tuberculosis or Hepatitis B: Experience from a single Asian centre. (August 2020) - Chan, Gloria HJ; Gwee, Yong Xiang; Low, Jia Li; Huang, Yiqing; Chan, Zhi Yao; Choo, Joan RE; Ngoi, Natalie YL; LE Ang, Yvonne; Muthu, Vaishnavi; Chong, Wan Qin; Wong, Alvin; Soo, Ross A.
Highlights: Reactivation of tuberculosis is possible in patients on immunotherapy. Outcomes may be improved with screening and treatment for latent tuberculosis. No increased adverse events in patients with hepatitis B infection. Tuberculosis and hepatitis B are not contraindications for immunotherapy. Abstract: Background: The importance of immune-checkpoint inhibitors (ICI) can no longer be understated since its move to front-line treatment in non-small cell lung cancer (NSCLC) in recent years. However, the safety and efficacy of ICI in special populations such as those with infections like tuberculosis (TB) and hepatitis B (HBV) remain unknown as they are routinely excluded from clinical trials. Methods: Records of patients with advanced NSCLC who were treated with ICI from January 2014 to June 2019 at a single Asian centre were reviewed. Those with a history of HBV and/or TB were selected. In this group, safety and treatment outcomes including overall survival (OS), progression-free survival (PFS) and response rate were reported and compared against control. Results: 191 patients received ICI, 47 (24.6%) had a history of TB/HBV. The median PFS in those with a history of TB/HBV was 5.7 months (95% CI 3.9-7.6), compared to 3.1 months (95% CI 2.4-3.8) in control (HR 0.61, 95% CI 0.39-0.93, p = 0.021). Median OS was 15.6 months (95% CI 10.2-21.0) compared to 11.1 months (95% CI 7.6-14.7 months) in the control group (HR 0.58, 95% CI 0.34-0.99, p = 0.046). Adverse events of any grade (G) were similar in both groups; slightly more patients with TB/HBV experienced G3 or higher adverse events. Four patients developed TB after initiation of ICI, none with previously documented TB experienced reactivation. Of the 42 patients with a history of HBV, eight had inactive chronic HBV and six had detectable viral load. None of the 34 patients who were previously exposed to HBV had reactivation. Conclusion: The use of ICI appears to be safe and efficacious in patients with TB/HBV infection. Prospective studies are required to identify those at risk in order to optimise care to these groups of patients.